1975
DOI: 10.1063/1.88359
|View full text |Cite|
|
Sign up to set email alerts
|

Infrared-pumped third-harmonic and sum-frequency generation in diatomic molecules

Abstract: Using molecular hydrogen as a model system, we present the first calculation which demonstrates the feasibility of efficient third-harmonic and sum-frequency generation of ir laser radiation by diatomic molecular gases. A conversion efficiency of 10% without phase matching is achievable with a modest laser intensity of about 20 MW/cm2. In addition to a two-photon resonance, the efficient conversion depends on a mechanism which makes use of virtual vibronic transitions exclusively. Possible methods for phase ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

1976
1976
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…Next, we introduce the formula for THG in diatomic molecules that is based on that in She and Billman [1,7]. The definitions of the variables are slightly different from those in [1].…”
Section: Theorymentioning
confidence: 99%
See 4 more Smart Citations
“…Next, we introduce the formula for THG in diatomic molecules that is based on that in She and Billman [1,7]. The definitions of the variables are slightly different from those in [1].…”
Section: Theorymentioning
confidence: 99%
“…The lowest-order process is third-harmonic generation (THG), which is similar to coherent anti-Stokes Raman scattering. Of the many theoretical and experimental studies on general THG, She and Billman [1] investigated the theory of using the vibrational states of diatomic molecules for THG and found that a high conversion efficiency of up to 30% could be expected in hydrogen gas using an optimized column density and an input laser intensity of 34 MW cm −2 . Palastro et al [2] discussed vibrational two-photon absorption and THG by nitrogen and oxygen and their effects on the propagation of ultrafast long-wave infrared pulses.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations